Features of seismic waves recorded by seismic exploration in 2002: Responses from valley structure of the bedrock beneath Mizuho Plateau - Yamada, Akira; Kanao, Masaki; Yamashita, Mikiya (National Institute of Polar Research, 2004)
P(論文) Seismic waves from natural sources were recorded in seismic exploration experiments in January 2002 by the 43rd Japanese Antarctic Research Expedition (JARE-43). Three kinds of seismic waves were recorded: (1) a teleseismic event occurred in the Kermadec Is. region, (2) local icequakes and (3) an unidentified event. The teleseismic waves show high signal-to-noise ratio in spite of the small magnitude of the event: this indicates that it is highly feasible to study not only the local shallow structure but also the deep structure of the earth by using teleseismic events. Frequency spectra of the waveforms show discordances along the observation line. The 2.0 Hz frequency component is very small in waveforms recorded by stations in the middle part of the observation line. On the other hand, the 1.5, 3.0 and 5.0 Hz frequency components are large in the records of these stations. These stations are located just above the valley topography of the interface between the ice sheet and the upper crust, which has been revealed by JARE-41 and JARE-43 seismological experiments. departmental bulletin paper